Hubungan Pengetahuan dan Sikap Ibu tentang Gizi, Asupan Protein dan Seng Anak, Serta Sanitasi Rumah Terhadap Stunting Anak Sekolah Dasar - Kholidah, Nur; Rahfiludin, M. Zen; P., Dina Rahayuning (Jurnal Ilmiah Mahasiswa, 2020)
Title :Relationship of mother's knowledge and attitudes about nutrition, and sanitation with stunting in elementary schoolBackground : Primary school periode is a time where children begin to enter school and know about the school environment. Stunting is a form of abnormal growth on children caused by long-term malnutrition and infectious diseases. The growth of elementary school of children requires intake of macro nutrients and micro nutrients. The purpose of this study was to determine the relationship between mother's knowledge and attitudes about nutrition, protein intake and zinc in children, and sanitation with stunting incidence in children on elementary school.Methods : Quantitative research methods with a cross sectional approach. The number of samples was 66 participants. Data analysis used chi square. Result : The analysis showed a correlation between mother's knowledge and attitudes about nutrition with the incidence of stunting (p <0.05) and the absence of a relationship between protein intake and children's zinc and home sanitation with the incidence of stunting (p> 0.05). However, confounding variables showed correlance between maternal height and history of infection with stunting (p <0.05). Conclusion : It is suggested that given the importance of knowledge and well attitudes from mothers regarding child development and nutrition,Â  is recommended that the health department provide information to mothers or prospective mothers regarding the importance of nutrition to children. It aims to minimize the incidence of stunting in children.